THE EFFECTIVENESS OF USING MOBILE PHONE APPLICATIONS IN VIRTUAL LABORATORIES ON ACADEMIC ACHIEVEMENT IN CHEMISTRY FOR STUDENTS OF THE DEPARTMENT OF CHEMISTRY COLLEGE OF EDUCATION OMDURMAN ISLAMIC UNIVERSITY - Hasb Allah, Abdelsalam Alkhider Ibrahim; Hewary, Olash Abdalrheem Albsheir (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The study aimed to reveal the effectiveness of using mobile phone applications in virtual laboratories on academic achievement in chemistry for students of the Department of Chemistry, In Faculty of Education, University of Omdurman Islamic. To achieve this, the study followed the semi-experimental and descriptive approaches, and the research community consisted of third-level students in the Department of Chemistry, Faculty of Education, Omdurman Islamic University and members of the teaching staff in the faculties of education at Omdurman Islamic University, the University of Khartoum and the Open University of Sudan, a sample of 40 third-level students representing 50% of the original population was randomly selected, and they were divided into two equal groups: an experimental group of 20 students and a control group of 20 students A sample of (15) faculty members. The researchers used the achievement test as a tool for data collection, using the appropriate methods of analysis, the data was analyzed by using the Statistical Package for Social Sciences (SPSS). The study concluded a set of results, the most important of which are: There are statistically significant differences between the mean scores of the experimental group that studied using the mobile phone in the virtual laboratories and the average scores of the control group that studied in the usual way at the levels of analysis and synthesis among the third-level students in the Department of Chemistry, Faculty of Education, Omdurman Islamic University, The results of the interview also showed that the mobile phone is effective and suitable in the educational process because of the programs it provides that support the educational process in all its aspects. Based on these results. The researchers recommended holding courses to train science teachers on the use of these programs in implementing laboratory activities in science curricula.